Linked Boundary Functions: Examining the Role of 'Research for Development' Organizations in Integrating Levels of Resource Governance. Issue 3 (4th March 2019) - Fudge, Maree; Hiruy, Kiros
Abstract: Natural resource management practices such as community-based resource management (CBRM) are well-established bottom-up approaches to developing adaptive governance systems. Less is understood about how communities involved in such processes can attract top-down support without compromising their credibility or salience. We tested the usefulness of the linked boundary functions concept – boundary chains – for explaining the role of "research for development" (R4D) organizations in the integration of bottom-up community resource governance and top-down policy and legislative governance. We used the Australian Centre for Agricultural Research (ACIAR) in the Solomon Islands as a case study to probe the role of R4D organizations in this regard. The linked boundary functions concept proved useful in exploring the active functions of R4D organizations as actors that lend credibility, salience, and legitimacy to community-based governance initiatives. The concept of linked boundary functions or boundary chains can contribute to the current discussion in the complexity-aware theory of change and open new avenues for boundary management that enable the development of integrated resource governance in complex development contexts. This article contributes to the existing literature on the boundary spanning activities of R4D organizations.